2005
DOI: 10.1007/s00125-005-0051-0
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone increases non-esterified fatty acid clearance in upper body obesity

Abstract: Aims/hypothesis: Plasma NEFA concentrations are largely determined by adipose tissue lipolysis. Insulin suppression of lipolysis is commonly impaired with insulin resistance and improves with thiazolidinedione treatment of type 2 diabetes. The present studies were designed to assess the effects of thiazolidinedione on NEFA (oleate) metabolism that are independent of improved glycaemic control. Materials and methods: We measured plasma oleate concentration and flux ([ H 2 ] glucose) and substrate oxidation (ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 47 publications
(75 reference statements)
2
22
1
Order By: Relevance
“…Our goal was to detect smaller, yet clinically relevant, effects of v-3 fatty acids on adipose tissue insulin resistance, such as those observed with a 10% weight loss due to a comprehensive lifestyle intervention. In a previous study that used this approach to help obese adults with insulin resistance, we found that insulin-suppressed fatty acid flux improved by 38% 6 46% and insulin-stimulated glucose disposal increased by 30% (35). Although not "normal," we estimated that this degree of improvement would be clinically meaningful, in line with the observations of Magkos et al (36).…”
Section: Power and Statistical Analysissupporting
confidence: 76%
“…Our goal was to detect smaller, yet clinically relevant, effects of v-3 fatty acids on adipose tissue insulin resistance, such as those observed with a 10% weight loss due to a comprehensive lifestyle intervention. In a previous study that used this approach to help obese adults with insulin resistance, we found that insulin-suppressed fatty acid flux improved by 38% 6 46% and insulin-stimulated glucose disposal increased by 30% (35). Although not "normal," we estimated that this degree of improvement would be clinically meaningful, in line with the observations of Magkos et al (36).…”
Section: Power and Statistical Analysissupporting
confidence: 76%
“…Upper-body subcutaneous fat is the source of excess systemic FFAs in both the fasted and fed conditions. Approaches to improving FFA metabolism in obesity include weight loss (71), inhibition of lipolysis (72), and thiazolidinediones (71).…”
Section: Discussionmentioning
confidence: 99%
“…plasma NEFA appearance when using these methodologies. However, insulin did not change the specific activity of plasma triglycerides during intravenous infusion of radioactive oleate tracer in humans (37). These potential limitations of our experimental design are therefore unlikely to have affected our conclusions.…”
Section: ͻ0001mentioning
confidence: 55%
“…This raises the possibility that high plasma NEFA levels observed in subjects with insulin resistance may display abnormal regulation of plasma NEFA clearance in addition to increased plasma NEFA appearance. Interestingly, the insulin-sensitizer pioglitazone lowers plasma NEFA concentration by increasing plasma NEFA clearance rate independently of change in plasma NEFA appearance in nondiabetic individuals with abdominal obesity (37).…”
Section: ͻ0001mentioning
confidence: 99%